2015
DOI: 10.1088/0026-1394/52/3/s123
|View full text |Cite|
|
Sign up to set email alerts
|

Uncertainties in gamma-ray spectrometry

Abstract: High resolution gamma-ray spectrometry is a well-established metrological technique that can be applied to a large number of photon-emitting radionuclides, activity levels and sample shapes and compositions. Three kinds of quantitative information can be derived using this technique: detection efficiency calibration, radionuclide activity and photon emission intensities. In contrast to other radionuclide measurement techniques gamma-ray spectrometry provides unambiguous identification of gamma-ray emitting rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 67 publications
0
35
0
2
Order By: Relevance
“…The measurement techniques employed are as follows: ionisation current measurements in a re-entrant ionisation chamber (IC) or a hospital calibrator (HIC) [31,32], net area analysis of full-energy γ-ray peaks (and integral spectrum counting) by γ-ray spectrometry with a HPGe detector (HPGe) [33], particle counting in a planar silicon detector in quasi-2πconfiguration (PIPS) [34], X-ray counting at a small defined solid angle with a gas-filled proportional counter (PC) [35,36], live-timed β–γ anti-coincidence counting (LTAC) [37], triple-to-double coincidence counting with a liquid scintillation vial and three photodetectors (TDCR) [38], liquid scintillation counting (LSC) [38], particle and photon counting in a sandwich CsI (Tl) spectrometer (CsI) [39], internal gas counting (IGC) [40], and α-particle counting at a small defined solid angle with a large planar silicon detector (αDSA) [35,36]. An overview of standardisation techniques and their sources of error can be found in the special issues 44(4) and 52(3) of Metrologia [41,42] and references in [25,28].…”
Section: Measurements and Analysismentioning
confidence: 99%
“…The measurement techniques employed are as follows: ionisation current measurements in a re-entrant ionisation chamber (IC) or a hospital calibrator (HIC) [31,32], net area analysis of full-energy γ-ray peaks (and integral spectrum counting) by γ-ray spectrometry with a HPGe detector (HPGe) [33], particle counting in a planar silicon detector in quasi-2πconfiguration (PIPS) [34], X-ray counting at a small defined solid angle with a gas-filled proportional counter (PC) [35,36], live-timed β–γ anti-coincidence counting (LTAC) [37], triple-to-double coincidence counting with a liquid scintillation vial and three photodetectors (TDCR) [38], liquid scintillation counting (LSC) [38], particle and photon counting in a sandwich CsI (Tl) spectrometer (CsI) [39], internal gas counting (IGC) [40], and α-particle counting at a small defined solid angle with a large planar silicon detector (αDSA) [35,36]. An overview of standardisation techniques and their sources of error can be found in the special issues 44(4) and 52(3) of Metrologia [41,42] and references in [25,28].…”
Section: Measurements and Analysismentioning
confidence: 99%
“…From Table 4 it can be observed that the combined standard uncertainty values varied by an order of magnitude among the participating laboratories. To further optimize the estimation of uncertainties in gamma-ray spectrometry measurements, dedicated work was been recently published by Cassette et al (2015) and by Lepy et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…A rigorous treatment of uncertainties in γ-ray spectrometry can be found in Lépy et al (2015). Complementary information can be found in Sima and Arnold (2009).…”
Section: Uncertainty On Etm Radionuclidesmentioning
confidence: 99%
“…(5) is simplified because assumes independence between the input variables but also because real spectra often present multiple interfering peaks from which the activity is evaluated using numerical methods. A complete formulation of the uncertainty associated to the activity of γ-emitters, including the evaluation of the covariance terms, can be found in Lépy et al (2015).…”
Section: Uncertainty On Etm Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation